Evaluating the change in vegetation cover in the city of Buraidah in the period from 2014 to 2024 Using geographic information systems and remote sensing: A case study of Qassim National Park - Aleairi, Samiayh Suliman (Journal of natural sciences, life and applied sciences, 2024)
The research aims to analyze and evaluate the impact of vegetation cover change in the city of Buraidah from 2014 to 2024 AD, analyze the causes influencing vegetation cover change in Qassim National Park, and evaluate its environmental condition, using geographical information systems and remote sensing to obtain quantitative information about vegetation cover using... Natural Vegetation Index (NDVI), and the descriptive analytical approach to develop a detailed description of the changes that occurred in the vegetation in the study area.Through the study, it was revealed that there was a significant increase in the area of vegetation in Qassim National Park, amounting to 2.4 km. This is a positive sign that reflects the efforts made to protect and develop the region, in addition to the presence of changes in the composition of plants in order to expand afforestation operations that contribute to improving biological diversity and enhancing awareness. Environmental awareness to the residents of the region of the importance of preserving the environment and sustaining natural resources.
Keywords: Qassim National Park; Buraidah; vegetation; salt acacia trees